Geografie di oggi. Metodi e strategie tra ricerca e didattica - Donadelli, Giovanni (Tratti geografici. Materiali di ricerca e risorse educative, 2015)
The volume offers new keys of interpretation and methodologies useful to understand the changes and the challenges of the contemporary world. The proposed geographical path is structured in four sections. A particular focus is on educational reality and the role of geography as a discipline able to train and educate a conscious and active citizenship.